Existence and Nonexistence of Positive Solutions for Fractional Three-Point Boundary Value Problems with a Parameter - Yunhong Li; Weihua Jiang (Journal of Function Spaces)
In this work, we investigate the existence and nonexistence of positive solutions for p-Laplacian fractional differential equation with a parameter. On the basis of the properties of Green’s function and Guo-Krasnosel’skii fixed point theorem on cones, the existence and nonexistence of positive solutions are obtained for the boundary value problems. We also give some examples to illustrate the effectiveness of our main results.